The Role of Estrogen Receptor β in the Dorsal Raphe Nucleus on the Expression of Female Sexual Behavior in C57BL/6J Mice - Sano, Kazuhiro; Morimoto, Chihiro; Nataka, Mariko; Musatov, Sergei; Tsuda, Mumeko C.; Yamaguchi, Naoko; Sakamoto, Toshiro; Ogawa, Sonoko (Frontiers in Endocrinology, 2018)
17-Estradiol (E2) regulates the expression of female sexual behavior by acting through estrogen receptor (ER) and . Previously, we have shown that ER knockout female mice maintain high level of lordosis expression on the day after behavioral estrus when wild-type mice show a clear decline of the behavior, suggesting ER may be involved in inhibitory regulation of lordosis. However, it is not identified yet in which brain region(s) ER may mediate an inhibitory action of E2. In this study, we have focused on the dorsal raphe nucleus (DRN) that expresses ER in higher density than ER. We site specifically knocked down ER in the DRN in ovariectomized mice with virally mediated RNA interference method. All mice were tested weekly for a total of three weeks for their lordosis expression against a stud male in two consecutive days: Day 1 with the hormonal condition mimicking the day of behavioral estrus, and Day 2 under the hormonal condition mimicking the day after behavioral estrus. We found that the level of lordosis expression in ER knockdown (ERKD) mice was not different from that of control mice on Day 1. However, βERKD mice continuously showed elevated levels of lordosis behavior on Day 2 tests, whereas control mice showed a clear decline of the behavior on Day 2. These results suggest that the expression of ERβ in the DRN may be involved in the inhibitory regulation of sexual behavior on the day after behavioral estrus in cycling female mice.